Iceland : 2014 Article IV Consultation and Fifth Post-Program Monitoring Discussions-Staff Report; Press Release; and Statement by the Executive Director for Iceland. (IMF Staff Country Reports; Country Report ;, 2015)
This 2014 Article IV Consultation highlights that Iceland has reached a relatively strong macroeconomic position with good growth prospects. Unemployment continues to trend down, now at 4 percent. Growth is expected to pick up to about 3 percent over 2015-17, supported by robust domestic demand and tourism. Consumption will be boosted by household debt relief and-together with net trade-will benefit from favorable commodity prices. Good progress has also been made in improving the financial stability framework, but gaps remain.